2020
DOI: 10.1007/s12182-020-00450-0
|View full text |Cite
|
Sign up to set email alerts
|

Scenario analysis on abating industrial process greenhouse gas emissions from adipic acid production in China

Abstract: Adipic acid is an important petrochemical product, and its production process emits a high concentration of greenhouse gas N 2 O. This paper aims to provide quantitative references for relevant authorities to formulate greenhouse gas control roadmaps. The forecasting method of this paper is consistent with the published national inventory in terms of caliber. Based on the N 2 O abatement technical parameters of adipic acid and the production trend, this paper combines the scenario analysis and provides a measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[ 18 ] that abatement was not implemented for the new adipic acid plants [ 19 ]. N 2 O abatement was also considered in NGHGIs [ 20 , 21 ], but the activity data they collected from the enterprise survey suggested that adipic acid production expanded largely in the meantime [ 22 ]. Based on the CDM reports during 2008 – 2012 ( https://cdm.unfccc.int/ ), this study assumed that only Henan Shenma Nylon Chemical Co., Ltd and PetroChina Company Limited Liaoyang Petrochemical Co. installed N 2 O abatement techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] that abatement was not implemented for the new adipic acid plants [ 19 ]. N 2 O abatement was also considered in NGHGIs [ 20 , 21 ], but the activity data they collected from the enterprise survey suggested that adipic acid production expanded largely in the meantime [ 22 ]. Based on the CDM reports during 2008 – 2012 ( https://cdm.unfccc.int/ ), this study assumed that only Henan Shenma Nylon Chemical Co., Ltd and PetroChina Company Limited Liaoyang Petrochemical Co. installed N 2 O abatement techniques.…”
Section: Discussionmentioning
confidence: 99%
“…ADPA is an important petrochemical commodity and its manufacturing process involves an emission source of greenhouse gases namely N 2 O [14]. ADPA is synthesized by HNO3 and is extremely harmful [15,16].…”
Section: Introductionmentioning
confidence: 99%